Invasion of Porcine Brain Microvascular Endothelial Cells by Streptococcus suis Serotype 2 - Vanier, Ghyslaine (American Society for Microbiology, 2004)
Streptococcus suis is an important swine pathogen that mainly causes meningitis and occasionally causes other infections, such as endocarditis, arthritis, and pneumonia. The pathogenesis of S. suis infection has not been completely defined. However, in order to cause meningitis, S. suis has to cross the blood-brain barrier (BBB) made up of brain microvascular endothelial cells. The objective of this work was to study the interactions of S. suis serotype 2 with porcine brain microvascular endothelial cells (PBMEC). The ability of North American and European S. suis serotype 2 strains to adhere to PBMEC and, most importantly, to invade PBMEC was demonstrated by using an antibiotic protection assay and was confirmed by electron microscopy. The polysaccharide capsule of S. suis seemed to partially interfere with the adhesion and invasion abilities of the bacterium. Our results showed that intracellular viable S. suis could be found in PBMEC up to 7 h after antibiotic treatment. Inhibition studies demonstrated that invasion of PBMEC by S. suis required actin microfilaments but not microtubular cytoskeletal elements or active bacterial RNA or protein synthesis. At high bacterial doses, suilysin-positive strains were toxic for PBMEC. The role of suilysin in cytotoxicity was confirmed by using purified suilysin, electron microscopy, and the lack of toxicity of a suilysin-negative mutant. In swine, the invasion of endothelial cells of the BBB could play an important role in the pathogenesis of the meningitis caused by S. suis.